Digital Transformation Understanding Business Goals, Risks, Processes, and Decisions - Cöster, Mathias (Open Book Publishers, 2023)
Whilst digitisation is far from a new concept, many assume that simply introducing automation and information systems in various forms will be enough to make their organisation's operations more efficient. This misconception can often lead to disarray and costly mistakes. Digital Transformation: Understanding Business Goals, Risks, Processes, and Decisions shows how to avoid such issues via careful consideration of what an enterprise really needs. Unlike many other books on digital transformation, the authors do not dwell on database design or the details of implementing information systems. Instead, they emphasise the importance of a clear understanding of all aspects of an organisation in order to effectively implement and manage digital systems, from business goals and strategies to structuring information and making decisions, risk assessments, project management, organising, and procuring services and products. Organised in eleven chapters, and drawing on examples from all over the world, this book will be of interest to university students of business administration, management, information systems, and computer science, as well as practitioners seeking to better understand how to handle digital transformation in their own organisation.